Feasibility analysis of Taijiquan as a way of national cultural soft power construction - Xi, Yongping; Xu, Pengzhan (The Journal of the International Society of Chinese Health Practices, 2021)
In response to the 19th National Congress Report and the 14th Five-Year Plan, this paper discusses the relationship between soft power and traditional Chinese culture. Finally, it is concluded that Taijiquan has the property of cultural soft power, and it is practicable to take Taijiquan as an effective way to enhance the national cultural soft power. It also puts forward effective countermeasures for the development of Taijiquan internationally: first, establishing a platform for Taijiquan exchange based on the country’s implementation of soft power strategy. Secondly, we should organize the cultural context of Taijiquan and implement the way to build soft power. Third, strengthen propaganda and enrich the means of dissemination of Taijiquan.Fourth, establishing a strategy for Taegeuk culture and enhancing the soft power of the country with Taegeuk culture as the main body.